Temporal adverbial clauses: A cross-linguistic perspective - Olguín Martínez, Jesús (Lingua Posnaniensis, 2023)
The study explores the form and function of ‘when’, ‘while’, ‘after’, ‘before’, and ‘until’ clauses in a variety sample of 218 languages. First, it is demonstrated that temporal adverbial clauses tend to be encoded with conjunctions and converbs in the database. A chi-squared goodness-of-fit test shows that ‘after’, ‘before’, and ‘until’ meanings are strongly and similarly associated with monofunctional clause-linking devices cross-linguistically. ‘While’ meanings are ambivalent, and ‘when’ meanings are strongly encoded with polyfunctional clause-linking devices. Second, the paper also explores the polyfunctionality patterns of temporal adverbial clause-linking devices. While the semantic polyfunctionality patterns attested in the present research align, for the most part, with those documented by other typological studies, there are a number of patterns that have been neglected in the typological literature, such as the polyfunctionality pattern between ‘while’ and ‘without’, between ‘after’ and ‘lest’, and between ‘before’ and ‘lest’, among others.